Species richness and functional structure of fish assemblages in three freshwater habitats: effects of environmental factors and management. Issue 4 (12th August 2019) - Queiroz‐Sousa, Jamile; Keith, Sally A.; David, Gianmarco S.; Brandão, Heleno; Nobile, André B.; Paes, Jaciara V. K.; Souto, Ana C.; Lima, Felipe P.; Silva, Reinaldo J.; Henry, Raoul; Richardson, Katherine
Abstract: In this study, the inverted trophic hypothesis was tested in the freshwater fish communities of a reservoir. The distribution of fish species in three freshwater habitats in the Jurumirim Reservoir, Brazil, was examined using both species richness and the relative proportions of different trophic groups. These groups were used as a proxy for functional structure in an attempt to test the ability of these measures to assess fish diversity. Assemblage structures were first described using non‐metric multidimensional scaling (NMDS). The influence of environmental conditions for multiple fish assemblage response variables (richness, total abundance and abundance per trophic group) was tested using generalised linear mixed models (GLMM). The metric typically employed to describe diversity; that is, species richness, was not related to environmental conditions. However, absolute species abundance was relatively well explained with up to 54% of the variation in the observed data accounted for. Differences in the dominance of trophic groups were most apparent in response to the presence of introduced fish species: the iliophagous and piscivorous trophic groups were positively associated, while detritivores and herbivores were negatively associated, with the alien species. This suggests that monitoring functional diversity might be more valuable than species diversity for assessing effects of disturbances and managements policies on the fish community.